Decision Supporter for Determining Priority in Supply of Shoe Raw Materials Using the Simple Additive Weighting Method - Ardila Sani; Tb Ai Munandar; Akip Suhendar (Universitas Serang Raya, 2019)
More and more types of raw materials will be used to expedite the shoe production process, making it difficult for companies to determine the priority of raw materials. So that there are often advantages and disadvantages of raw materials during the production process, which causes changes in the budget of production costs that are not in accordance with the initial plan, resulting in decreased corporate profits. Decision Support System (SPK) is a system that can help someone in making decisions that are accurate and right on target. Many problems can be solved by using SPK, one of which is determining priorities in the supply of raw materials. There are several methods that can be used in building a DSS, including simple addtive weighting (SAW). The Simple Additive Weighting (SAW) method is often also known as the weighted sum method, by finding the weighted sum of performance ratings for each alternative of all attributes. This study discusses the making of a decision support system as a tool for determining priorities in the supply of raw materials using the simple additive weighting (SAW) method. This application was developed with the Power Builder 8.0 programming language and Sybase SQL Anyware 5.0 as its database. The results of this study are able to help system users determine the priority of the supply of raw materials in order to facilitate the production process.